Personalized notification agent for examination timetable / Nor Azizah Shaharudin - Shaharudin, Nor Azizah (2010)
Personalize notification agent for the examination timetable developed to give notification to student about their examination timetable. The system will provide examination information to student that contains the examination date, venue and time. The implementation, which follows Extreme programming (XP) methodology will produced prototype that implements personalized notification agent in Microsoft Windows Vista's sidebar gadget.